1987
DOI: 10.1021/bi00379a023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence analysis of complementary DNA encoding rat mammary gland medium-chain S-acyl fatty acid synthetase thio ester hydrolase

Abstract: Poly(A)+ RNA from pregnant rat mammary glands was size-fractionated by sucrose gradient centrifugation, and fractions enriched in medium-chain S-acyl fatty acid synthetase thio ester hydrolase (MCH) were identified by in vitro translation and immunoprecipitation. A cDNA library was constructed, in pBR322, from enriched poly(A)+ RNA and screened with two oligonucleotide probes deduced from rat MCH amino acid sequence data. Cross-hybridizing clones were isolated and found to contain cDNA inserts ranging from app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The data base search revealed that ORF1 and ORF2, as shown previously for GRST (30), were also similar to predicted vertebrate thioesterase II enzymes from duck (DFAT [45]) and rat (RFAT [47]) which can transfer and thus catalyze release of fatty acids from multifunctional synthetase complexes (Table 2 and Fig. 8).…”
Section: And Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The data base search revealed that ORF1 and ORF2, as shown previously for GRST (30), were also similar to predicted vertebrate thioesterase II enzymes from duck (DFAT [45]) and rat (RFAT [47]) which can transfer and thus catalyze release of fatty acids from multifunctional synthetase complexes (Table 2 and Fig. 8).…”
Section: And Discussionsupporting
confidence: 76%
“…2. GRST, grsT gene product (30); RFAT, rat medium-chain fatty acid thioesterase (47); DFAT, duck medium-chain fatty acid thioesterase (45); Ac Tr (yeast), yeast acetyltransferase (50); P/M Tr (yeast), yeast palmytl/malonyltransferase (50); Ac/M Tr (chicken), chicken acetyl/malonyltransferase (11); EryA(1 to 3), three thioesterase motifs predicted from the erythromycin synthetase gene sequence (12); ACVS, ACV synthetase from A. nidulans (55).…”
Section: And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some specialized tissues, such as nonruminant mammary glands [2,3] and avian uropygial glands [4], a discrete monofunctional monomeric protein, thioesterase II, catalyses the hydrolysis of medium-chain fatty acids from the fatty acid synthase. The amino acid sequences of both the thioesterase I domain of the rat fatty acid synthase [5] and the thioesterase II enzyme from lactating rat mammary gland [6,7] have been determined, and their cDNAs have been cloned. The two types of chain-terminating enzyme share some common structural features and appear to be distantly related [5].…”
Section: Introductionmentioning
confidence: 99%
“…TE II has broad substrate specificity and interacts with FAS to hydrolyze the fatty acyl thioesters before they mature to longerchain acids. The cDNA sequences of the TE Ils of the rat mammary gland (6) and of the uropygial gland of mallard ducks (7) have been reported. We recently showed by site-directed mutagenesis that the Ser10'l and His274 of TE I are important in its mechanism of action (2,3).…”
mentioning
confidence: 99%